Deficiency of ADA2 (DADA2) - Hülya Köse; Sara Şebnem Kılıç (Güncel Pediatri)
Deficiency of Adenosine Deaminase 2 (DADA2) is a systemic disorder that is inherited in an autosomal recessive manner. Initially identified as a monogenic form of systemic vasculitis that mirrors polyarteritis nodosa (PAN), DADA2 is attributed to biallelic pathogenic variants in the adenosine deaminase 2 gene (ADA2; formerly known as CECR1) on chromosome 22q11. DADA2 presents with variable symptoms that can manifest as vasculitis, immune dysfunction, or hematological abnormalities. The primary disease phenotypes consist of polyarteritis nodosa (PAN)-like vasculitis, Diamond-Blackfan anemia (DBA)-like hematologic findings, and immunodeficiency. The vasculitic condition often manifests through severe ischemic or hemorrhagic strokes that can be life-threatening. To confirm the diagnosis of DADA2, it is imperative to analyze the ADA2 gene and measure low or unnoticeable ADA2 activity in plasma or serum. The use of anti-tumor necrosis factor agents has proven to be efficacious in treating patients with an inflammatory phenotype. Hematopoietic stem cell transplantation (HSCT) stands out as a promising treatment alternative for patients presenting with predominant hematologic or immunologic manifestations.